2007
DOI: 10.1097/01.nna.0000302386.76119.22
|View full text |Cite
|
Sign up to set email alerts
|

Developing Leaders at Every Level

Abstract: The shortage of frontline nursing staff and their managers in acute care organizations necessitates strategies to both use and recognize the unique knowledge and skills of these individuals. The authors describe one organization's successful implementation of a shared decision-making structure that promotes an empowering work environment in which professional fulfillment and personal satisfaction can flourish. With support and opportunity, leaders are developed across all levels of nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…17(p47) Research had demonstrated that leadership development programs can result in increased PE. [34][35][36][37] Thus, continued development of leaders to strengthen their PE is needed in both academia and practice settings. The NM role is one of the most challenging leadership roles in healthcare.…”
Section: Implications For Practicementioning
confidence: 99%
“…17(p47) Research had demonstrated that leadership development programs can result in increased PE. [34][35][36][37] Thus, continued development of leaders to strengthen their PE is needed in both academia and practice settings. The NM role is one of the most challenging leadership roles in healthcare.…”
Section: Implications For Practicementioning
confidence: 99%
“…An environment that creates a proactive culture with committed employees and a higher level of work satisfaction is predisposed to generating a higher quality of patient care (Laschinger, 2008) and better patient outcomes (Kowalik & Yoder, 2010;Moore & Hutchison, 2007).…”
mentioning
confidence: 99%
“…Factors contributing to nursing vacancies and turnover include unsupportive practice environments, long work hours, an aging workforce, and excessive physical and psychological demands (AACN, 2012). A management style such as shared governance that emphasizes the decisional involvement (DI) of nurses has been associated with enhancement of the nursing practice environment (Kowalik & Yoder, 2010; Moore & Hutchison, 2007; Weston, 2008) and improved health care organizational outcomes (Kowalik & Yoder, 2010; Kramer et al, 2009; Moore & Hutchison, 2007; Weston, 2008). Enhancing nurse involvement in the decision-making process contributes to nurse retention and recruitment (Havens & Vasey, 2003), empowers nurses to take control of their practice, and may act as a starting point in addressing the nursing shortage caused from vacancies and turnover.…”
mentioning
confidence: 99%
See 2 more Smart Citations